DISCOURSE STRATEGIES IN PROMOTING SUSTAINABLE AGRICULTURE: A MULTICULTURAL APPROACH BY THE SOLOK RADJO FARMER COOPERATIVE - Khaira, Intan Nabila; Sarmiati, Sarmiati; Azwar, Azwar (ppjbsip, 2025)
This study explores the persuasive communication strategies employed by the Solok Radjo Farmers' Cooperative to promote sustainable agricultural practices and multicultural values. Using Fairclough's discourse analysis framework, the research examines how language, metaphors, and narratives are utilized in individual and group contexts to influence farmer behavior and perceptions. Data collected through in-depth interviews, field observations, and document analysis reveal a multifaceted communication approach that aligns with local cultural norms. At the individual level, managers adopt personalized language, employing local idioms and emotional appeals to build trust and resonate with farmers personal experiences. In group settings, inclusive discourse and cultural symbols emphasize collective responsibility and solidarity, fostering a sense of shared purpose. Key strategies include metaphors, such as comparing land stewardship to family care, and success narratives that highlight tangible benefits of sustainable practices. These strategies not only facilitate the adoption of sustainable methods but also create a cohesive community identity grounded in multicultural values. The findings underscore the importance of tailoring communication to cultural and social contexts to enhance the effectiveness of sustainability initiatives. Insights from this study offer practical guidance for cooperatives globally, illustrating how culturally sensitive communication can advance sustainability goals and strengthen community cohesion.